A Three-Year Study of Campylobacter jejuni Genotypes in Humans with Domestically Acquired Infections and in Chicken Samples from the Helsinki Area - Hänninen, Marja-Liisa (American Society for Microbiology, 2000)
Campylobacter jejuni isolates from stool samples of patients with domestically acquired sporadic infections and from chicken from retail shops were studied during seasonal peaks from June to September over a 3-year period from 1996 to 1998. A large number of pulsed-field gel electrophoresis (PFGE) genotypes (a combined SmaI-SacII pattern) were identified each year. Certain genotypes persisted for the whole study period, and predominant genotypes represented 28 to 52% of the strains during a restricted period of time. The peak level of positive chicken samples was between July and August of each study year, when 10 to 33% of the samples were positive for campylobacter. The same PFGE genotypes found in humans were also detected in the chicken samples. This suggests that common genotypes were circulating in the area.